Housing Benefits in the System of Social Security Law of the Czech Republic and Their Constitutional and European Union Aspects - Gabriela Halířová (Societas et Iurisprudentia)
The paper deals with housing benefits from the perspective of view of their enshrining in the system of the Czech social security law. It points out their anchoring in two different types of social security, the problematic aspects arising from this and the mutual relationship of benefits. Also, the paper deals with whether the entitlement to housing benefits can be subsumed under the social rights guaranteed by the Charter of Fundamental Rights and Freedoms, and whether persons migrating within the European Union are entitled to housing benefits too.